2017
DOI: 10.1590/s0100-736x2017000200012
|View full text |Cite
|
Sign up to set email alerts
|

Intake and digestibility in sheep fed on marandu grass silages added with dehydrated barley

Abstract: The objective was to evaluate the intake and the apparent digestibility in sheep fed on marandu grass silages added with dehydrated barley. Twenty crossbred Santa Inês lambs were used, with a mean initial weight of 30±4.5 kg and mean age of 14±2 months. The experimental sheep were distributed into a completely randomized design and lining, with five treatments and four repetitions, with treatments levels of inclusion of 0, 10, 20, 30 and 40% natural matter of naturally dehydrated brewery residue for 36 hours t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Possibly, the reduction in the intake of CP, from the level of 153.8 g/kg DCBM, is associated with the intake of DCBM in silage, because the proportion of soybean meal was reduced by up to 66% in the concentrate. Ferreira et al (2017) also found a quadratic effect on the intake of CP in sheep fed grass silage with dry by‐product with a high protein content.…”
Section: Discussionmentioning
confidence: 91%
“…Possibly, the reduction in the intake of CP, from the level of 153.8 g/kg DCBM, is associated with the intake of DCBM in silage, because the proportion of soybean meal was reduced by up to 66% in the concentrate. Ferreira et al (2017) also found a quadratic effect on the intake of CP in sheep fed grass silage with dry by‐product with a high protein content.…”
Section: Discussionmentioning
confidence: 91%
“…Aumentar la cantidad de guineo cuadrado en los ensilados disminuyó la digestibilidad de la fibra; pero la calidad de la mezcla total se incrementó por el aporte de carbohidratos no fibrosos a los ensilados, lo que mejoró el valor relativo del forraje, que en consecuencia mejoró el aporte de nutrimentos al animal (Ferreira et al, 2017).…”
Section: Componentes De La Pared Celular En Los Ensiladosunclassified
“…Regions with tropical climate have many genera of grasses (Pennisetum, Panicum, Cynodon, and Brachiaria) that can be recommended for silage; among them, the grasses of the genus Brachiaria can be highlighted due to their high potential for biomass production, their adaptation to low soil fertility, and low pH tolerance [1]. However, the silage of these grasses may not result in the silage of good nutritional quality due to the high moisture content (approximately to 80%), low water-soluble carbohydrates (lower than 1% dry matter, DM), and high buffering power (greater than 20 EQ-HCl) on the 70th day, which is the best time for harvesting [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Byproducts from cereal and food processing may have characteristics that make them viable for inclusion in the grass silage process [2] such as the soybean hulls produced as a byproduct of the soybean industry and which can be considered a potential additive to be included in the grass silage process, due to its high water retention capacity, which limits the development of Clostridium spp. and allows a rapid drop in pH, so when included in Brachiaria decumbens silage (BDS), this byproduct improves the fermentation and nutritional value of the silage, despite presenting low water-soluble carbohydrates.…”
Section: Introductionmentioning
confidence: 99%